The representation of land and landownership in medieval Icelandic texts - Taylor, L; Laura Taylor (2006)
﻿ This thesis investigates the representation of land and landownership in medieval Icelandic texts. I shall demonstrate that there is scant homogeneity in this representation; the variation between different narratives is startling and unusual. I seek to categorise this variability by identifying the lack of a secure tradition surrounding land and landownership, and exploring the possibilities open to the saga author to use land practices and myths as literary devices or to glorify the past. I also examine variability caused by the differences in the realm of 'actual' experience. I shall explore a range of narratives, from stories of the initial settlement of Iceland, to issues of inheritance, to conveyance and to dispute over territory. The last chapter takes a flip-side view of landownership to consider the representation of the landless of family saga narrative. The texts which I shall examine are the Íslendingasögur, Landnádmabók and Íslendingabók. Throughout the thesis I also make reference to Grágás for illumination and comparison. In the first and second chapters I also include archaeological evidence for discussion.